2022
DOI: 10.46298/lmcs-18(1:8)2022
|View full text |Cite
|
Sign up to set email alerts
|

A Recursive Approach to Solving Parity Games in Quasipolynomial Time

Abstract: Zielonka's classic recursive algorithm for solving parity games is perhaps the simplest among the many existing parity game algorithms. However, its complexity is exponential, while currently the state-of-the-art algorithms have quasipolynomial complexity. Here, we present a modification of Zielonka's classic algorithm that brings its complexity down to $n^{O\left(\log\left(1+\frac{d}{\log n}\right)\right)}$, for parity games of size $n$ with $d$ priorities, in line with previous quasipolynomial-time solutions. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This problem is still intensely studied due to its broad applications. It also is one of the few problems which canonically lie in NP ∩ coNP (even in UP ∩ coUP [19]), with recent breakthroughs achieving quasi-polynomial algorithms [4,14,28].…”
Section: Synthesis and Gamesmentioning
confidence: 99%
“…This problem is still intensely studied due to its broad applications. It also is one of the few problems which canonically lie in NP ∩ coNP (even in UP ∩ coUP [19]), with recent breakthroughs achieving quasi-polynomial algorithms [4,14,28].…”
Section: Synthesis and Gamesmentioning
confidence: 99%
“…More recently, a quasi-polynomial version was devised by Parys [32] through an ingenious pruning of the recursion tree. This was later refined by Lehtinen et al [30], who observed that the tree of recursive calls follows a particular construction of universal trees. Subsequently, Jurdziński and Morvan [26] generalized it to a generic algorithm parameterized by a universal tree.…”
Section: Introductionmentioning
confidence: 97%
“…Most research has focused on parity games: as the most special class of games, algorithms have the option to use the special structure of their problems, and they are most directly linked to the synthesis and verification problems mentioned earlier. Parity games have thus enjoyed a special status among graph games and the quest for efficient algorithms [13,11,26,38,7,37,27,4,3] for solving them has been an active field of research during the last decades, which has received further boost with the arrival of quasi-polynomial techniques [8,18,15,23,24,10].…”
Section: Introductionmentioning
confidence: 99%